Morphometric changes in the renal tissue of offspring rats born under experimental diabetes mellitus conditions on days 3, 60, and 90 - Mamadalieva , Odinabobu; Tilyabov , Ikrom (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In connection with the widespread prevalence of this condition, the number of people with diabetes mellitus (DM) continues to increase steadily. According to the latest data from the International Diabetes Federation (IDF), by the year 2030 the number of adults aged 20 to 79 with diabetes worldwide is expected to reach 439 million.